РЕДКОЕ НАБЛЮДЕНИЕ ТРЕХ СЛУЧАЕВ ALG1-CDG (CDG-1k) В ОДНОЙ СЕМЬЕ - Гусина, Ася Александровна; Гусина, Нина Борисовна; Румянцева, Наталья Владимировна; Зиновик, Александр Валентинович (Медицина: теория и практика, 2020)